Agricultural Biotechnology Research Capacity in Four Developing Countries - Falconi, César A. (International Service for National Agricultural Research, 1999)
In 1998, ISNAR conducted a biotechnology research indicator survey in the four national agricultural research systems of Mexico, Kenya, Indonesia, and, Zimbabwe to provide an overview of their agricultural biotechnology research capacities. The findings reveal several factors that limit the development of such a capacity. Advanced biotechnology techniques were being used in only a few public sector research organizations, and most organizations were still in the first stages of developing their capacity. The focus of most research activities was on crops, with a limited number concentrating on livestock. Although expenditures for research grew annually in each country, the number of researchers grew much faster, and expenditures remained small when compared to total research expenditures. The public sector accounted for most of total expenditures (92% on average), while private sector participation remained limited. Although agricultural biotechnology received some government attention, a comprehensive strategy for the development of biotechnology was still lacking in the sampled countries. Some of the policy recommendations for overcoming these limitations include increasing investment in agricultural biotechnology research, promoting private-sector involvement, fostering collaboration between the public and private sectors, and designing a comprehensive strategy for the development of biotechnology.